Pharmacokinetics, Safety, and Antiviral Effects of Multiple Doses of the Respiratory Syncytial Virus (RSV) Fusion Protein Inhibitor, JNJ-53718678, in Infants Hospitalized With RSV Infection: A Randomized Phase 1b Study. (23rd March 2020) - Martinón-Torres, Federico; Rusch, Sarah; Huntjens, Dymphy; Remmerie, Bart; Vingerhoets, Johan; McFadyen, Katie; Ferrero, Fernando; Baraldi, Eugenio; Rojo, Pablo; Epalza, Cristina; Stevens, Marita
Abstract: Background: This phase 1b study evaluated the pharmacokinetics, safety, and antiviral effects of the respiratory syncytial virus (RSV)–specific fusion inhibitor JNJ-53718678 (JNJ-8678) in hospitalized RSV-infected patients aged > 1 to ≤24 months. Methods: Patients categorized by age (cohort 1: ≥6 to ≤24 months; cohort 2: ≥3 to < 6 months; cohort 3: > 1 to < 3 months) were randomized to oral JNJ-8678 or placebo once daily for 7 days. Dose increases followed data review committee recommendations (cohort 1: 2/6/8/9 mg/kg; cohort 2: 1.5/4.5/6 mg/kg; cohort 3: 1/3/5 mg/kg). Cohort 1 included a 9 mg/kg dose, as target exposures were not reached at lower doses. Sparse pharmacokinetic samples were assessed using population pharmacokinetics modeling. Safety was assessed by adverse events (AEs), laboratory tests, and electrocardiograms. To assess antiviral effects, RSV RNA viral load from nasal swabs was quantified over time using reverse-transcription quantitative polymerase chain reaction. Results: Patients received JNJ-8678 (n = 37) or placebo (n = 7). Pharmacokinetic parameters were similar at the highest doses for cohorts 1–3 (area under the plasma concentration–time curve from time of administration up to 24 hours postdosing at day 7: 35 840, 34 980, and 39 627 ng × hour/mL, respectively). Two grade 3 AEs were reported (both bronchiolitis; 1 JNJ-8678, 1 placebo), reported as serious AEs; all other AEs were grade 1 or 2. Two additional serious AEs were reported (rhinitis [JNJ-8678]; pneumonia [placebo]). No deaths, grade 4 AEs, or AEs leading to discontinuation were reported. Median RSV viral load change from baseline in JNJ-8678 vs placebo by day 3 was −1.98 vs −0.32 log10 copies/mL. Conclusions: In RSV-infected infants, JNJ-8678 was well tolerated. Target exposures were reached and antiviral activity was observed. Clinical Trials Registration: NCT02593851. Abstract : Treatment options directed toward respiratory syncytial virus (RSV) are limited. This first-in-child dose-escalation study of the direct-acting RSV antiviral treatment JNJ-53718678, demonstrated the potential for effective regimens, with an acceptable safety profile, to treat pediatric patients with RSV infection.